Quantitative analysis of the structural dynamics of mitotic chromosomes in live mammalian cells - Mora-Bermúdez, Felipe (2006)
Chromatin, organized into individual chromosomes, is the physiological carrier of the genetic and epigenetic information in eukaryotes. In the nucleus of an intact cell, the structure of chromatin is dynamic and essential for genomic activities. The most dramatic changes in chromatin structure occur in mitosis, when compact metaphase chromosomes are formed, organized and partitioned equally to two daughter cells. How this vital reorganization of chromatin is accomplished remains poorly understood in vivo. To address this, in the first part of my thesis I developed quantitative assays to determine the kinetics of mitotic chromosome compaction, using multidimensional confocal microscopy of live cells stably expressing fluorescent histone 2b. Condensation was measured at three different scales: Large-scale (~800 nm), where the chromatin volume was measured by high resolution 4D imaging; medium scale (~200 nm) by statistical analysis of pixel intensities; and molecular scale (~10 nm) by a FRET reporter of histone tail environment. These measurements show that (i) mitotic compaction may start at least 20 min before prometaphase; (ii) it correlates with changes in histone tail conformation; (iii) chromatin density is not highest in metaphase but in late anaphase chromosomes. In the second part, I focused on the novel finding of highest compaction in anaphase. Single chromosome measurements revealed that chromatids compact in anaphase by a mechanism of lengthwise shortening that starts only after segregation of the sister chromatids is complete. This axial shortening was not affected in condensin-depleted cells, and was independent of the poleward pulling motion on kinetochores, but it nevertheless depended on dynamic microtubules. Perturbation of this shortening caused a severe phenotype of multi-lobulated daughter nuclei, strongly suggesting a function in post-mitotic nuclear assembly and architecture. In addition, if anaphase compaction was perturbed in condensin-depleted cells, segregation defects increased 3-fold, suggesting a second role for anaphase compaction as a rescue mechanism for segregation defects. In the third part, the quantitative compaction assays were used to probe the role of PNUTS, a major protein phosphatase 1 nuclear-targeting subunit, in the regulation of chromatin structure. In live cells depleted of PNUTS by RNAi, compaction was slowed at least 3-fold. Our collaborators in the group of Philippe Collas at the University of Oslo had shown that PNUTS accelerates chromatin decompaction in vitro. PNUTS is thus involved in mitotic chromatin structure in vivo and in vitro, and my findings make it an interesting target for future research to understand the molecular mechanism of chromosome compaction.
Keywords: Hochschulschrift